Heat capacity measurement of C14–ZrMn2 and thermodynamic re-assessment of the Mn–Zr system. (March 2020) - Kuprava, A.; Saenko, I.; Fabrichnaya, O.
Abstract: The CALPHAD approach was used to derive thermodynamic parameters of the Mn–Zr system based on experimental results and critical evaluation of available data. Novel ab-initio calculations as well as experimental data on enthalpy of formation and heat capacity measurements for the C14–ZrMn2 Laves phase were taken into account. The congruent melting point of the C14–ZrMn2 Laves phase was determined using differential thermal analysis (DTA) at 1765 K. Data on heat capacity for the C14–ZrMn2 phase were extended to high temperature range up to 980 K using differential scanning calorimetry (DSC). Standard entropy for C14–ZrMn2 was calculated using an extended Einstein model based on newly obtained results. Additionally, the sublattice model based on antisite substitution in the C14–ZrMn2 Laves phase has been used in order to describe its homogeneity range. Based on the currently obtained results and novel literature data, thermodynamic parameters for the Mn–Zr system were re-optimized. The self-consistent thermodynamic description derived in the present work reproduces all experimental data well. Highlights: Heat capacity of the C14–ZrMn2 phase is measured in 200–980 K temperature interval. Standard entropy of the C14–ZrMn2 phase is calculated. Phase equilibria are studied in the Zr–Mn system (melting temperatures, invariant reactions). Thermodynamic parameters are optimized and reproduce experimental data.